Primer Conteo de aves en la Provincia de Cotopaxi, Cantón la Maná - Calo Chanaluisa, Nataly Silvana (2019)
The importance of carrying out a bird count in different urban and rural spaces has allowed the development of this type of events to increase in recent years, in the Cotopaxi Province there are several bird registration, however It has not yet known consolidated the information that evidences its potential, there fore it is important to carry out a pre-counting that gives rise to the Christmas bird counting, for which it relied on the methodology of the Audubon that contributed to the development of the bird counting, first a 24km radius was drawn in the round, which allowed the identification of the following strategic counting points that were; Machay, Garden of Dreams, Los Laureles, Cascadas, Ñungañan, and La Esperanza, by describing the points, it was possible to identify that the La Esperanza sector is not within the limits of La Maná Canton, but that they are within territorial limits of Cantón Pujilí, each of the points are in different altitude ranges from 170 to 2100 meters above sea level, which has allowed the counting to be feasible at each of the points already mentioned when identifying the different physical characteristics, the geographical coordinates helped to obtain and design a descriptive map of the area supported by the ARCGIS software; next, the discounting was carried out, which consists of the meeting of each leader in the designated points for the collection and identification and number of species that were registered in all the counting points in which they registered 220 species of birds were registered, of which they have been taxonomically classified, the information was finally systematized obtaining a database of each of the species registered to there by load the information on the e-platform. - Bird, but due to the importance that I represent and there fore to the proximity to the Canton they were considered within the study area; It is recommended to follow up with a bird counting, considering the same points and methodology applied in the event held.